Peranan Subsektor Perikanan dalam Perekonomian Wilayah Jawa Barat - Istiqlaliyah Muflikhati; Narni Farmayanti; Gatot Yulianto (Buletin Ekonomi Perikanan, 1996)
One of the criteria in deciding the priority of a regional economic development is the level of linkage (back&lard and forward linKage) of a given sector and the level of multiplier effect of income and employment. The objective of this study is to investigate the role of fishery subsektor in economic regional of West Java, the level of linkage with the other sectors an the level of income and employment multiplier effect.Data showed that the contribution o( fishery subsector to PORB of West Java is relatively small, namely 1,08% in 1988 and 1,17% in 1993. At tha sama period fishery subsector contributed 1,93% and than decreasing until 1,89% for available employment in West Java.The result of study with input-output (1-0) model showed that linkage of fishery subsector is relatively low, except inland fishery sector had backward linkage is relavely high. Inland fishery sector have the income multiplier effect is relatively high, Whereas marine fishery and salted-fish and dried-fish bussiness is low. Generally, fishery subsector have the employment muttiplier is relatively low. Regarding the potention of fishery is relatively big, whereas the level of its exploitation have not been optimal, so fishery subsector is important to be a priority in regional economic development in West Java. And so, in order that the level of linkage of fishery subsector is relatively high, it is important to grow fisheriesagroindustries in West Java.